EKSPLORASI DAN IDENTIFIKASI MINAT SERTA BAKAT ANAK BERDASARKAN PERKEMBANGAN USIA DAN PERAN LINGKUNGAN PENDIDIKAN PADA SETIAP JENJANG SEKOLAH - Nur Wahyuni; Pujana Saputri; Cindy Fatika Sari Lubis; Perti Wahyuni Halawa; Naomi Gulo; Nofrianus Zai; Lestari Larosa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to examine and identify children's interests and talents based on the stages of age development, as well as analyze the role of non-formal education in supporting the development process. The research was carried out at Sanggar Deli Nusantara using a descriptive qualitative approach. Data was collected through observation, interviews, and documentation by involving elementary school and junior high school (SMP) students, activity coaches, and parents as research informants. The findings of the study show that there are differences in the development of children's interests according to the age phase. Children at the elementary level are at the exploratory stage with a tendency to try various activities, while students at the junior high school level are starting to show more directed and consistent interest. Identified talents include verbal-linguistic, dramatic-expressive, interpersonal, intrapersonal, creative-imaginative, and leadership skills. The non-formal education environment plays a role as an adaptive and supportive learning space in increasing children's confidence, intrinsic motivation, and social skills. In addition, parental support is an important factor in maintaining the sustainability of children's potential development. The results of the study confirm that the development of interests and talents is a gradual process influenced by the development of age, the quality of the learning environment, and family involvement. Thus, non-formal education has a strategic role in supporting the development of children's potential in a comprehensive and sustainable manner.